Knowledge of Ebola virus disease among students at AIMST University, Kedah, Malaysia (Medical Journal of Indonesia, 2019)
BACKGROUND To assess the level of knowledge of Ebola virus disease (EVD) among students at The Asian Institute of Medical, Science and Technology (AIMST) University. METHODS This research is a cross-sectional study of 250 year-1 to year-4 students selected through the stratified sampling method from five health science faculties at AIMST University. Independent variables included students' age, gender, faculty of origin, source of information, and participation in seminars or conferences, while the dependent variable was the students' knowledge of EVD. Data were obtained using a self-administered questionnaire. RESULTS The majority of the students did not have adequate knowledge of EVD (77.2%). The level of knowledge of EVD was significantly associated with faculty of origin (p = 0.014) only and not associated with other variables, such as sociodemographic factors, source of information, and participation in seminars or conferences. CONCLUSIONS Information on EVD needs to be disseminated more intensively among university students due to the current lack of knowledge of the disease.